Muslim Ummah of 7th century to the OIC; the Evolution of OIC in the History of Islam - Ali, Tajwar; Sultan, Haseena; Ali, Tahira; Batool, Usmat (Pakistan Journal of Humanities and Social Sciences, 2024)
The current OIC is the product of the core concept of Islam which was presented before 1400 years in the Arabian Peninsula by the Holy Quran and the Hazrat Muhamad. This concept of one Ummah united the Muslims in the history in different ways. This research paper examines the development of the OIC in the historical backdrop of the Muslim Umah from the 7th century to the present. This study investigates the origins and evolution of the notion of a cohesive Muslim community, commencing with the formative era of Islam led by Prophet Muhammad. It explores the subsequent changes and adaptations that this concept has undergone throughout the centuries. This research examines the socio-political and theological factors that shaped the creation of the OIC in 1969, emphasizing significant events and individuals that played a role in its development. It seeks to gain a thorough grasp of the relevance of the OIC and its impact on the worldwide Muslim population by using a historical and analytical approach. The findings demonstrate the intricate nature and accomplishments of the OIC in promoting harmony and collaboration among its member states while maneuvering through the varied and frequently disputed realm of global affairs. This study enhances the wider discussion on Islamic solidarity and global institutions, providing valuable perspectives on the continued significance and difficulties faced by the OIC in the contemporary era.